Factors influencing students' interest to pursue music teaching as a career choice / Farah Adibah Mohd Isa - Mohd Isa, Farah Adibah (Faculty of Music, 2016)
The purpose of this study was to investigate the factors influencing students' interest to pursue music teaching as a career choice among Music Education students in the Faculty of Music, UiTM Shah Alam. Specifically, this study looked at two (2) elements: external factors influencing students' interest to pursue music teaching as a career choice and internal factors influencing students' interest to pursue music teaching as a career choice. The sample comprised of 73 students from one program in the Faculty of Music, UiTM Shah Alam which was the Music Education (MU220) program. Subjects were asked to complete a survey and rate factors influences on the selection of the students in pursuing music teaching as their career choice. Survey results indicated that for external factors 54.8% of the students said that their parents give them moral support to study at UiTM while for internal factors 74.0% of the students said that they really enjoy music.